Dissemination and Implementation of Character Strengthening Learning Technology Modules - Noviana Desiningrum; Endang Nuryasana; Mustadji Mustadji; Andi Mariono (Basic and Applied Education Research Journal, 2022)
This study aims to analyze the process of dissemination and simultaneous implementation of instructional technology teaching materials based on character strengthening using the Dick and Carey model. This research was using the method of steps 8 and 10 of Borg and Gall's development research. The results of this study were the language aspects in this module were accepted by the readers and users (5.69), the teaching material's systematics were very good (8.75) in integrating the Dick and Carey models and the character reinforcement integration in the teaching material's systematics was in very good (9.13). The lecturers' ability in applying teaching materials was in very good (4.04); the students' character in the lecture was excellent (4.06); the student's understanding and mastery was in very satisfying (84.03) with very good (97%) classic completeness value; and student's response to think-point share learning is 83.55%. This study concluded that the language aspect in this module is accepted by both the readers and users in terms of students and lecturers.